2013
DOI: 10.1371/journal.pone.0059378
|View full text |Cite|
|
Sign up to set email alerts
|

Nanosized TiO2-Induced Reproductive System Dysfunction and Its Mechanism in Female Mice

Abstract: Recent studies have demonstrated nanosized titanium dioxide (nano-TiO2)-induced fertility reduction and ovary injury in animals. To better understand how nano-TiO2 act in mice, female mice were exposed to 2.5, 5, and 10 mg/kg nano-TiO2 by intragastric administration for 90 consecutive days; the ovary injuries, fertility, hormone levels, and inflammation-related or follicular atresia-related cytokine expression were investigated. The results showed that nano-TiO2 was deposited in the ovary, resulting in signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 51 publications
8
94
0
2
Order By: Relevance
“…An interesting finding of the present study was that resveratrol treatment in ob/ob mice resulted in a decrease of the number of atretic follicles. Because high TNF-a, IL-6, and androgen levels may promote follicular atresia (13,24,66), resveratrol could ameliorate this predominant ovarian event through the decrease of T and these proinflammatory cytokines. Likewise, it has been reported that resveratrol may inhibit apoptosis of oocytes (32), thus follicles may be rescued from undergoing atresia.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding of the present study was that resveratrol treatment in ob/ob mice resulted in a decrease of the number of atretic follicles. Because high TNF-a, IL-6, and androgen levels may promote follicular atresia (13,24,66), resveratrol could ameliorate this predominant ovarian event through the decrease of T and these proinflammatory cytokines. Likewise, it has been reported that resveratrol may inhibit apoptosis of oocytes (32), thus follicles may be rescued from undergoing atresia.…”
Section: Discussionmentioning
confidence: 99%
“…24 The ovarian injury may be associated with alteration of inflammation-related or follicular-atresia-related cytokine expression. 25 In addition, gold NPs can enter Chinese hamster ovary cells through the endocytic pathway, 26 infiltrate rat ovarian granulosa cells and subcellular organelles, and alter in vitro estrogen accumulation. 27 Moreover, mitogen-activated protein kinase cellular signal transduction pathways in mammalian cells can be activated by silicon carbide nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, serum parameters, sex hormone levels and atretic follicle count increased, and inflammation and necrosis were observed. In addition, inflammation-related or follicular atresia-related cytokine expressions were altered, which shows that fertility reduction and ovary injury of mice is associated with inflammatory factors [36].…”
Section: Effects Of Tio 2 Nanoparticle On Female Reproductive Systemmentioning
confidence: 96%